MOTHERS' CONTRIBUTIONS TO ISLAMIC RELIGIOUS EDUCATION AMID THE CHALLENGES OF GLOBALIZATION - Defi Lia Amanda (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
The era of globalization has brought rapid social, cultural, and technological changes that have impacted the educational process within families, particularly Islamic religious education. Children now live in a digitally connected world, filled with the flow of information, and vulnerable to global cultural influences that do not always align with Islamic values. In this context, mothers, as the first and primary educators in the family, play a crucial role in instilling Islamic values ​​in children. This study used a library research approach, analyzing various academic literature (published in at least 2020) related to the role of mothers, Islamic religious education, family education, and the challenges of globalization. The results indicate that mothers' contributions to Islamic religious education include role modeling, fostering worship habits, monitoring digital media, religious communication, instilling morals, creating a religious culture within the home, and collaborating with educational institutions. Key challenges include the influence of digital technology, the penetration of global culture, changes in modern family structures, and mothers' limited digital literacy. Strengthening mothers' capacities through digital literacy, increasing religious understanding, and synergy between families, schools, and communities is necessary to ensure that Islamic religious education within the family remains relevant and effective amidst globalization.